Purposes and Challenges of Integrating ICT in English Language Teaching in Nepalese Context - Bhattarai, Prakash (LPPM Universitas Lancang Kuning. Pekanbaru. Indonesia, 2021)
This phenomenological study explores how English language teachers become information and communication technology (ICT) literate and why they make use of ICT in English language class and find out challenges in integrating ICT in English language teaching (ELT). For this purpose, two secondary-level English teachers were selected purposively, and in-depth interviews were conducted to collect data. The collected data were analyzed using the thematic analysis technique. The findings drawn from the lived experience of the teachers reveal that teachers become ICT literate and updated by taking formal classes, training, and teaching their students; they make use of ICT in ELT for students' language development, motivation, and autonomy. The challenge of keeping the students on the right track is the major challenge English language teachers encounter while integrating ICT in ELT. Though there are challenges, every English language teacher should try to teach the English language integrating ICT.